2022
DOI: 10.3390/ani12162021
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Porcine Circovirus 1/2/3 and Genetic Analysis of Porcine Circovirus 2 in Wild Boar from Jiangxi Province of China

Abstract: A number of disorders that harm pig production are linked to porcine circoviruses, including PCV2. PCV2 infection is a substantial contributor to porcine-circovirus-associated illnesses (PCAS) and the post-weaning multi-systemic wasting syndrome (PMWS), which have a significant negative economic impact on pig production. Additionally, PCV infection has been labeled as a global concern to cattle and wildlife. This study’s objectives were to examine the prevalence of PCV1/2/3 in Jiangxi Province, China, and to c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 36 publications
2
9
2
Order By: Relevance
“…Although we cannot rule out the possibility of other influences, these rapidly increasing positive rates of PCV3 in this study might be due to sample differences (Kixmöller et al., 2008 ; J. Zhang et al., 2022 ). Our results showed that the positive rate of PCV3 in wild boar (5.5% in HLN) was much lower than that in Europe (40.4%–77.4%) (Klaumann et al., 2019 ; Prinz et al., 2019 ), but similar to that in China (5.79%) (Hu et al., 2022 ). Previous studies have suggested that wild boar might have an important role as a reservoir in PCV3 prevalence (Hu et al., 2022 ; Klaumann et al., 2019 ; Prinz et al., 2019 ).…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Although we cannot rule out the possibility of other influences, these rapidly increasing positive rates of PCV3 in this study might be due to sample differences (Kixmöller et al., 2008 ; J. Zhang et al., 2022 ). Our results showed that the positive rate of PCV3 in wild boar (5.5% in HLN) was much lower than that in Europe (40.4%–77.4%) (Klaumann et al., 2019 ; Prinz et al., 2019 ), but similar to that in China (5.79%) (Hu et al., 2022 ). Previous studies have suggested that wild boar might have an important role as a reservoir in PCV3 prevalence (Hu et al., 2022 ; Klaumann et al., 2019 ; Prinz et al., 2019 ).…”
Section: Discussionsupporting
confidence: 61%
“…Our results showed that the positive rate of PCV3 in wild boar (5.5% in HLN) was much lower than that in Europe (40.4%–77.4%) (Klaumann et al., 2019 ; Prinz et al., 2019 ), but similar to that in China (5.79%) (Hu et al., 2022 ). Previous studies have suggested that wild boar might have an important role as a reservoir in PCV3 prevalence (Hu et al., 2022 ; Klaumann et al., 2019 ; Prinz et al., 2019 ). However, considering the quarantine situation in South Korean pig farms, a correlation with wild boars and domestic pigs in PCV2 and PCV3 prevalence is relatively low.…”
Section: Discussionsupporting
confidence: 61%
“…Another report showed the prevalence of PCV1/-2/-3 in wild boar in Jiangxi province. Of 138 wild boar samples, the positive rates of PCV1, PCV2, and PCV3 were 21.7%, 22.5%, and 5.8%, respectively [ 34 ]. Consistent with our data, the above study showed that the positive rates of PCV1 and PCV2, and PCV2 and PC3 co-infections were 7.3% and 3.6%.…”
Section: Discussionmentioning
confidence: 99%
“…To analyze the genomic sequence of PCV1, PCV2 and PCV3, the full-length ORF genes and genomes of PCVs isolates were amplified using Taq DNA polymerase (TaKaRa, Dalian, China) as described previously ( Cao et al., 2018 ; Hu et al., 2022 ; Xia et al., 2019 ; Wen et al., 2018 ), the PCR amplicons were separated by electrophoresis on a 1% agarose. The bands were extracted and purified using the AxyPrep DNA Gel Extraction Kit (AxyGene, USA).…”
Section: Methodsmentioning
confidence: 99%